CUSUM: a dynamic tool for monitoring competency in cataract surgery performance. Issue 4 (30th November 2009) - Salowi, Mohamad Aziz; Choong, Yee-Fong; Goh, Pik-Pin; Ismail, Mariam; Lim, Teck-Onn
Abstract : Aims: To apply cumulative sum (CUSUM) in monitoring performance of surgeons in cataract surgery and to evaluate the response of performance to intervention. Method: A CUSUM analysis was applied to 80 phacoemulsification performed by three ophthalmic trainees and one consultant, for the occurrence of posterior capsular rupture and postoperative refracted vision of worse than 6/12 among patients without pre-existing ocular comorbidity. The CUSUM score of each consecutive procedure performed by an individual surgeon was calculated and charted on CUSUM chart. When trainees' CUSUM charts showed an unacceptable level of performance, their supervisors would give feedback and impose closer monitoring of subsequent surgeries. Results: CUSUM charts of the trainees demonstrated an initial upward followed by flattening trend. This reflects learning curves in their process of acquiring competency in phacoemulsification. In contrast, the consultant showed a flat curve indicating an ongoing maintenance of competence. Conclusion: The CUSUM analysis is able to monitor and promptly detect adverse events and trends of unacceptable outcomes in cataract surgery. This objective and dynamic monitoring makes CUSUM a useful audit tool for individual surgeons, but more so for busy consultants who need to supervise trainees.